2020
DOI: 10.1007/s12011-020-02447-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Zn/Se and α-Tocopherol Supplementation on Metabolic Milieu, Haemogram and Semen Traits of Breeding Stallions

Abstract: Trace element status and metabolic milieu are sometimes overlooked in common veterinary clinical practice across animal species. The evaluation of requirements of trace elements, in fact, may be useful to prevent the perturbation of tissue-specific metabolic impair. In particular, essential trace elements in the diet play key roles within sub-cellular metabolic patterns with macro effects at the systemic level, like blood cell stability and semen quality. This effect was studied in breeding stallions, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…However, taking into account scientific studies carried out on other species (Cardenia et al, 2011 ; Voljč et al, 2011 ), the α‐tocopherol levels—natural isoform of the fat‐soluble vitamin E group—in tissues and plasma were significantly influenced by the level of dietary supplementation, leading to higher stability of meat lipids. Moreover, Cappai, Pudda et al, ( 2020 ); Cappai, Taras et al, ( 2020 ) recommended to monitor the Vitamin E intake in the context of adequate feeding practices for health and welfare assessment. In particular, since α‐tocopherol is synthesised and stored chiefly in the green plants, the same authors suggested that a higher dietary intake of Vitamin E is important in stabled horses when they are fed on hay.…”
Section: Discussionmentioning
confidence: 99%
“…However, taking into account scientific studies carried out on other species (Cardenia et al, 2011 ; Voljč et al, 2011 ), the α‐tocopherol levels—natural isoform of the fat‐soluble vitamin E group—in tissues and plasma were significantly influenced by the level of dietary supplementation, leading to higher stability of meat lipids. Moreover, Cappai, Pudda et al, ( 2020 ); Cappai, Taras et al, ( 2020 ) recommended to monitor the Vitamin E intake in the context of adequate feeding practices for health and welfare assessment. In particular, since α‐tocopherol is synthesised and stored chiefly in the green plants, the same authors suggested that a higher dietary intake of Vitamin E is important in stabled horses when they are fed on hay.…”
Section: Discussionmentioning
confidence: 99%
“…Nolazco Sassot et al, 2018, conducting a study on Thoroughbreds, indicate changes in specific plasma lipids through supramaximal exercise that could be useful to formulate a specific equine diet [13]. In this regard, the role of micronutrients was widely explored in prevention of fatty acid oxidation in all the membranes of the cellules [14]. There are only a few studies focusing on fatty acids, but they seem to be limited by either including a small number of samples or not always reporting the same cohort of fatty acids, focusing only on PUFAs (ω3 and ω6) and not considering the rest of the lipid classes [15].…”
Section: Introductionmentioning
confidence: 99%